Optical characteristic study of monolayer VS2 based on first-principles calculations. (October 2017) - Ding, Zhiyuan; Peng, Junhao; Xie, Xing; Hu, Jianwei; Yang, Hanqi; Wu, Fugen; Dong, Huafeng
Abstract: Monolayer VS2 has two common stable phases, 2H-phase and 1T-phase. Based on first-principles calculations, we studied the optical properties of 2D-VS2, including their dielectric functions, absorption coefficients, refraction indexes and energy loss functions. Also, we fully analyzed the relationship between the electronic structure and the optical characteristics of 2D-VS2 . We found that the differences of density of states are the fundamental reasons for the differences of the two phase optical absorption behavior. Highlights: The optical properties of 2D-VS2 are studied systematically, helping the applications of 2D-VS2 in optoelectronic devices. Clarified the relationship between the electronic structure and the optical characteristics of 2D-VS2 . The difference of density of states is the reason for the difference of the two phases optical absorption behavior.